Estimation of the Efficacy of Retroperitoneoscopic Renal Cysts Deroofing - Sh. T. Mukhtarov; F. A. Akilov; D. Kh. Mirkhamidov; B. A. Ayubov (Вестник урологии)
Introduction. The intensive introduction of modern endovideosurgical techniques creates the prerequisites for the further expansion of minimally invasive surgical interventions. Literature reviews` data on the results of retroperitoneoscopic operations suggest that endovideosurgery in urology has broad prospects for further development.Purpose of the study. To estimate of the efficacy and safety of the retroperitoneoscopic operations for renal cysts.Materials and methods. Retroperitoneoscopic operations (renal cysts deroofing) were performed for 152 symptomatic patients with Bosniak I kidney cysts (from 4.4 х 3.8 cm to 14.5 х 14.0 cm). Proposal of the operations were classified according to the technical difficulty as “Easy” in 147 (96.7%) cases (Е: sum of scores 3-5), in 5 (3.3%) cases – «Slightly difficult» (SD: score 7). Statistical analyses of the results performed by the program Microsoft Office Excel 2007, StatSoft Statistica 8.0 with using the Student-Fisher`s criteria.Results. The mean duration of the operations was 35.7 ± 6.1 min (30-90 min); there were not any intraoperative complications; the mean blood loss was 23.0 ± 4.1 ml (10-100 ml); there was no need for blood transfusion; incidence of postoperative complications were 2.4% - in 4 cases there were manifestation of urinary tract infection during the postoperative period (II category of the complications according to Clavien-Dindo classification); mean hospital stay was 2.2 ± 0.1 day (1-6 days); drainages were removed on second postoperative day; there were not any conversions to open operations and additional procedures in postoperative period.Conclusions. Retroperitoneoscopic renal cysts deroofing is effective and safe procedure for the treatment of simple kidney cysts. This method has the advantages of minimal invasiveness, minimal complications, short in hospital stay and fast recovery of the patients.The study did not have sponsorship. The authors have declared no conflicts of interest.